Biological Activity of Macrocyclic Complexes of 3D Series Transition Metal Ions (International Journal of Scientific Research in Science and Technology, 2025)
Transition metal macrocyclic complexes have been extensively studied by researchers in search of designing new chemical agents because of their excellent biological activities, including antimicrobial, antioxidant and anticarcinogenic. Presence of metal ions accelerates the drug action and efficiency of organic therapeutic agents. Transition metal complexes based on hydrazides of carboxylic acids have displayed wide range of biological and pharmaceutical activities because of the formation of –CONH- linkage which is used as building unit for peptides formation from amino acids in biological systems. It also gives higher stability to the molecules because of the presence of a chelatophore group of donor atoms in the coordination sphere. In previous paper we studied about synthesis and characterization of macrocyclic complex of 3D series transition metal ions and present paper discussed about the biological activity of macrocyclic complex.